2015
DOI: 10.1111/iju.12796
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between uroflowmetry and sonouroflowmetry in recording of urinary flow in healthy men

Abstract: Abbreviations & Acronyms PCC = Pearson's correlation coefficient Q ave = average flow rate Q max = maximum flow rate SUF = sonouroflowmetry UF = uroflowmetry Objectives: To evaluate the accuracy of sonouroflowmetry in recording urinary flow parameters and voided volume. Methods: A total of 25 healthy male volunteers (age 18-63 years) were included in the study. All participants were asked to carry out uroflowmetry synchronous with recording of the sound generated by the urine stream hitting the water level in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 5 publications
(13 reference statements)
0
37
0
Order By: Relevance
“…In their study using 25 male volunteers, the flow pattern showed a good visual correlation between the 2 methods. However, Qmax showed a weak correlation (PCC = 0.38) and Qavg, voided volume showed moderate correlation (PCC = 0.57 and PCC = 0.68, respectively) [8]. In female patients, Qmax showed a weak correlation between uroflowmetry and sonouroflowmetry (PCC = 0.38) [9] after analyzing 183 re-cordings of 36 healthy female volunteers.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In their study using 25 male volunteers, the flow pattern showed a good visual correlation between the 2 methods. However, Qmax showed a weak correlation (PCC = 0.38) and Qavg, voided volume showed moderate correlation (PCC = 0.57 and PCC = 0.68, respectively) [8]. In female patients, Qmax showed a weak correlation between uroflowmetry and sonouroflowmetry (PCC = 0.38) [9] after analyzing 183 re-cordings of 36 healthy female volunteers.…”
Section: Discussionmentioning
confidence: 94%
“…Sound-based analysis of uroflowmetry has been tried previously. The technical concept of sonouroflowmetry was introduced in 2009 [3] and clinical trials of sonouroflowmetry in male and female patients were reported in 2015 and 2016, respectively [8,9]. In their study using 25 male volunteers, the flow pattern showed a good visual correlation between the 2 methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an extendable wand can deploy the urinalysis strip toward the potential location of the female urine stream. Another approach for implementing the uroflowmetry module is sonouroflowmetry, which uses sound to estimate the urine flow rate and volume 60 . Sonouroflowmetry can be implemented for both male and female users, in sitting or standing positions, while avoiding optical scans of the user's body parts.…”
Section: Current Limitationsmentioning
confidence: 99%
“…An artificial spike of high‐intensity sound, which occurred at the beginning of each recording, was detected and eliminated. Subsequently, the matching datasets of UF and SUF were compared with respect to the following parameters: flow time recorded using UF was compared to the duration of the sound signal recorded by SUF; UF recorded voided volume was compared to the calculated area under the SUF curve; and UF recorded maximal flow rate (Q max ) was compared to the peak intensity of the sound signal …”
Section: Methodsmentioning
confidence: 99%